Effective evaluation of the exact relativistic plasma dispersion functions - Pavlov, S.S.; Castejón, F.; Tereshchenko, M. (Вопросы атомной науки и техники, 2013)
A new effective evaluation method of the exact relativistic plasma dispersion functions in the real and complex regions is given on the basis of nonsingular forms of Cauchy or Cauchy-type integrals and the Euler-Maclaurin formula.